Application of Foot Massage to Hemodynamic Stability in Ventilator-Adjusted Patients - Afiffah Arundina Zakarisma; Sri Rahayu (Sarana Ilmu Indonesia (salnesia), 2026)
Critically ill patients undergoing medical care in the ICU experience disruption of the body's physiological regulatory mechanisms, which can lead to hemodynamic instability. Efforts to maintain hemodynamic stability can be managed through pharmacological and non-pharmacological therapy. One form of non-pharmacological intervention that has the potential to affect hemodynamic status in patients treated in the ICU is foot massage. This study was conducted to analyze hemodynamic changes in patients using ventilators after being given a foot massage. This case study was conducted using a descriptive plan. The research subjects consisted of 4 patients using ventilators in the ICU. Foot massage was given for 40 minutes every day for two days, where before the foot massage was given an average systolic blood pressure of 154.0 mmHg. Diastolic 82.38 mmHg, MAP 105.75 mmHg, RR 23.5 beats/min, pulse rate 95.13 beats/min and SpO2 98%. The results of the study after foot massage for 2 days showed an improvement in hemodynamic status after foot massage, which was indicated by an average Systolic 147.38 mmHg, Diastolic 82.25 mmHg, MAP 103.75 mmHg, RR 21.63 beats/min, Pulse 89.88 beats/min, and SpO2 99%. This case study concludes that foot massage provides positive changes in the hemodynamic status of critical patients using ventilators in the ICU.